Causes and consequences of diachronous V-shaped ridges in the North Atlantic Ocean - Parnell-Turner, Ross; White, Nicky; Henstock, Timothy J.; Jones, Stephen M.; Maclennan, John; Murton, Bramley J. (Journal of Geophysical Research: Solid Earth, 2017)
Author Posting. © American Geophysical Union, 2017. This article is posted here by permission of [publisher] for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research: Solid Earth 122 (2017): 8675–8708, doi:10.1002/2017JB014225. In the North Atlantic Ocean, the geometry of diachronous V-shaped features that straddle the Reykjanes Ridge is often attributed to thermal pulses which advect away from the center of the Iceland plume. Recently, two alternative hypotheses have been proposed: rift propagation and buoyant mantle upwelling. Here we evaluate these different proposals using basin-wide geophysical and geochemical observations. The centerpiece of our analysis is a pair of seismic reflection profiles oriented parallel to flow lines that span the North Atlantic Ocean. V-shaped ridges and troughs are mapped on both Neogene and Paleogene oceanic crust, enabling a detailed chronology of activity to be established for the last 50 million years. Estimates of the cumulative horizontal displacement across normal faults help to discriminate between brittle and magmatic modes of plate separation, suggesting that crustal architecture is sensitive to the changing planform of the plume. Water-loaded residual depth measurements are used to estimate crustal thickness and to infer mantle potential temperature which varies by ±25°C on timescales of 3–8 Ma. This variation is consistent with the range of temperatures inferred from geochemical modeling of dredged basaltic rocks along the ridge axis itself, from changes in Neogene deep-water circulation, and from the regional record of episodic Cenozoic magmatism. We conclude that radial propagation of transient thermal anomalies within an asthenospheric channel that is 150 ± 50 km thick best accounts for the available geophysical and geochemical observations. NERC Grant Number: NE/G007632/1; Girdler Fund, University of Cambridge; BP Exploration 2018-05-14